PENGARUH PERAN GANDA TERHADAP KINERJA PEGAWAI PEREMPUAN MELALUI STRESS KERJA PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI SULAWESI TENGGARA - Aninna Mulyawati Baridin; Patwayati Patwayati; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this study is to examine and explain the effect of multiple roles on employee performance through work stress. This research approach is quantitative with a positivist paradigm. Data collection were carried out in a cross-sectional manner using a questionnaire. The population of this study were 54 female employees at the regional development planning agency of the province of southeast sulawesi office. The analytical tool used is Partial Least Square.The results of the study indicate that : (1) multiple roles have a positive and significant effect on employee performance, (2) multiple roles has a positive and significant effect on work stress, (3) work stress has a positive and significant effect on employee performance, (4) multiple roles has a positive and significant effect on employee performance through work stress